2017
DOI: 10.1038/ejhg.2017.99
|View full text |Cite
|
Sign up to set email alerts
|

Yunis-Varón syndrome caused by biallelic VAC14 mutations

Abstract: Yunis-Varón syndrome (YVS) is an autosomal recessive disorder comprising skeletal anomalies, dysmorphism, global developmental delay and intracytoplasmic vacuolation in brain and other tissues. All hitherto-reported pathogenic variants affect FIG4, a lipid phosphatase involved in phosphatidylinositol (3,5)-bisphosphate [PtdIns(3,5)P] metabolism. FIG4 interacts with PIKfyve, a lipid kinase, via the adapter protein VAC14; all subunits of the resulting complex are essential for PtdIns(3,5)P synthesis in the endol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…The role of Ca 2+ release via TRPML1 can be seen in FIG4 KO fibroblasts where partial rescue of the vacuolation phenotype can be achieved in these cells by incubation with the small molecule synthetic activator of TRPML1, ML-SA1 ( [ 46 ] and see Results section). Furthermore, and consistent with disruption of PIKfyve activity, fibroblasts taken from a patient with a biallelic loss-of-function variant in VAC14 were recently reported to contain numerous swollen cytoplasmic vacuoles, a phenotype that was also partially rescued by ML-SA1 [ 24 ]. Although a similar rescue of vacuolation with ML-SA1 was not reported following pharmacological inhibition of PIKfyve in HeLa cells [ 2 ], this apparently negative finding could be explained by the much shorter incubation time used, 2 h in HeLa cells compared to 24 h or longer with the FIG4 KO and VAC14 patient cells [ 24 , 46 ].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The role of Ca 2+ release via TRPML1 can be seen in FIG4 KO fibroblasts where partial rescue of the vacuolation phenotype can be achieved in these cells by incubation with the small molecule synthetic activator of TRPML1, ML-SA1 ( [ 46 ] and see Results section). Furthermore, and consistent with disruption of PIKfyve activity, fibroblasts taken from a patient with a biallelic loss-of-function variant in VAC14 were recently reported to contain numerous swollen cytoplasmic vacuoles, a phenotype that was also partially rescued by ML-SA1 [ 24 ]. Although a similar rescue of vacuolation with ML-SA1 was not reported following pharmacological inhibition of PIKfyve in HeLa cells [ 2 ], this apparently negative finding could be explained by the much shorter incubation time used, 2 h in HeLa cells compared to 24 h or longer with the FIG4 KO and VAC14 patient cells [ 24 , 46 ].…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, and consistent with disruption of PIKfyve activity, fibroblasts taken from a patient with a biallelic loss-of-function variant in VAC14 were recently reported to contain numerous swollen cytoplasmic vacuoles, a phenotype that was also partially rescued by ML-SA1 [ 24 ]. Although a similar rescue of vacuolation with ML-SA1 was not reported following pharmacological inhibition of PIKfyve in HeLa cells [ 2 ], this apparently negative finding could be explained by the much shorter incubation time used, 2 h in HeLa cells compared to 24 h or longer with the FIG4 KO and VAC14 patient cells [ 24 , 46 ]. Whether this implies an effect beyond simply modulating the amount of fusion and fission of lysosomes is unclear.…”
Section: Discussionmentioning
confidence: 82%
“…It was recently shown that mutations in VAC14 can also be associated with Yunis–Varón syndrome (Lines et al 2017). Mutations in the lipid phosphatase gene FIG4 are also associated with Yunis–Varón syndrome, along with Charcot–Marie–Tooth disease Type 4J, a peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Yunis–Varón syndrome (MIM#216340) presents with profound neonatal onset of hypotonia, failure to thrive, skeletal anomalies, and feeding intolerance. This can also include profound developmental delay, absent reflexes, persistent ophisthotonus, roving eye problems, severe feeding intolerance, skeletal abnormalities, heart defects, limb defects, cataracts, structural brain anomalies, and episodes of irritability (Lines et al 2017). A more recent study presented an additional four families with variants in FIG4, in which the ocular findings in each affected child in Family 4 were initially described as bull's eye maculopathy (Lenk et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, two patients with a severe neurodegenerative phenotype of progressive debilitating dystonia, loss of motor milestones and deep gray matter changes on brain MRI, characterized as striato-nigral degeneration, childhood-onset (MIM ), were reported to have biallelic (compound heterozygous) mutations in VAC14 (Lenk et al, 2016). In addition, one patient with YVS (discussed below) harbored mutations in VAC14 (Lines et al, 2017). Taken together, these data suggest that mutations in FIG4 and VAC14 result in depletion of PtdIns(3,5)P2 via the loss of PIKFYVE activity (despite the role of FIG4 as a 5-phosphatase) and are associated with similar severe neurodegenerative phenotypes.…”
Section: Neuromuscular Diseases – Disorders Of the Peripheral Nerve Amentioning
confidence: 99%